The Evaluation of Learning Online and Its Influence on Improving The Quality of Student Learning in the Covid-19 Pandemic - Abdul Rahman; Mardi Mardi; Zainal Zainal; Andi Asrijal; Asriadi Asriadi (Universitas Cokroaminoto Palopo, 2021)
This research aimed to determine the Evaluation of Learning Online and Its Influence on Improving the Quality of Student Learning in the Covid-19 pandemic. The method of this research used the CIPP evaluation model. Data collected by using questionnaires and interviews. Analysis data used quantitative and qualitative descriptive. The results showed that the context aspect regarding the media and learning facilities that lecturers use in online learning is an appropriate category according to the needs and convenience of students in accessing the application. The input aspect regarding students' understanding of the use of online applications in learning, the quality of the material delivered by the lecturer in an online class, regarding the facilities is in the appropriate category and quite good. The process aspect regarding activities between lecturers and students, obstacles in the learning process, the use of online learning facilities, and the implementation of the learning system are well or appropriate. However, it still needs to get more attention from the teaching staff, especially since the assessment process for students is sometimes still subjective. The product aspect regarding the impact of knowledge possessed by students and lecturers about the use of online learning applications and the results of the implementation of learning is appropriate or good enough. So the conclusion is the four aspects of CIPP evaluation (context, input, process, product) that researcher used in evaluating online learning are in the appropriate category (Effective enough), and it gives a positive impact on improving the quality of students, especially in the process of using online learning applications and According to the lecturer, further learning will combine offline and online so that students can make this a new habit in the learning process.